Acolhimento na atenção básica : navegações e mergulhos nos discursos e práticas produzidos no cotidiano de uma unidade de saúde da família - Hoffmann, Catharina (2009)
This research discusses the plans of health production processes, aiming the health discourses and practices related to embracement. The context for the analysis is the Primary Health Care in the city of Vitória/ES and the research field are the everyday activities of the Family Health Service in Ilha do Príncipe. As reference it was used Institutional Analysis and Collective Health. It was analyzed the way how workers embrace the users of the health service as well as listened to their conceptions and discourses produced upon embracement, in relation to their everyday practices, which includes work processes and the interaction with the users. It was used Cartography as the methodological strategy. Data was produced from February 2008 to September 2008, through field observation, field diary and interviews with the users and health workers from the Family Health Service. The results show that the process of work and its management are fragmented and bureaucratized. There is the intention, from the workers, to revise the work processes, however they find obstacles in this practice. Concerning Embracement, the requirements the workers have to fulfill to obtain a certain amount of productivity is one aspect that compromises the quality of the relation between the Family Health Teams and their relation towards the users, affecting the response to their needs and the offer of actions in health care. The everyday activities show that the needs the workers are willing to welcome are related to disease or symptoms physically expressed. It was revealed that users have conversation as a valued demand and it is embraced by some workers. It was highlighted that communication in the Family Health Teams is restricted to discussions on administrative issues and procedures. The informal hierarchy order according to the level of graduation contributes to understand Embracement as an activity or procedure attributed to a specific category (nursing assistants), which supposedly have the technical capacity to do it in the action of receiving the user in the establishment. It was noticed that there isn t a pact between the actions in health offered and the users, in a way that the Family Health Program doesn t guarantee embracement. However, the tension in the everyday relations between worker and user favor the discussion of embracement as an action that may surpass reception. It is evident the need of reorganizing the process of work and engendering subjectivities for a humanization that values the singularization processes in a way of promoting a real democracy in the access to health, in the quality of health care and in the guarantee of the principles of SUS (Public Health System)